2018
DOI: 10.1002/jcp.26552
|View full text |Cite
|
Sign up to set email alerts
|

Compromised regulation of the collecting duct ENaC activity in mice lacking AT1a receptor

Abstract: ENaC-mediated sodium reabsorption in the collecting duct (CD) is a critical determinant of urinary sodium excretion. Existing evidence suggest direct stimulatory actions of Angiotensin II (Ang II) on ENaC in the CD, independently of the aldosterone-mineralocorticoid receptor (MR) signaling. Deletion of the major renal AT receptor isoform, AT R, decreases blood pressure and reduces ENaC abundance despite elevated aldosterone levels. The mechanism of this insufficient compensation is not known. Here, we used pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…ENaC activity was assessed using previously published procedures, detailed in Supplement. Female and male SD rats, bred and studied at Medical College of Georgia at Augusta University, were fed grain‐based vivarium chow (Teklad Irradiated Rodent Diet 8904) and studied under baseline conditions and after infusion of AngII as described in Protocol 1.…”
Section: Methodsmentioning
confidence: 99%
“…ENaC activity was assessed using previously published procedures, detailed in Supplement. Female and male SD rats, bred and studied at Medical College of Georgia at Augusta University, were fed grain‐based vivarium chow (Teklad Irradiated Rodent Diet 8904) and studied under baseline conditions and after infusion of AngII as described in Protocol 1.…”
Section: Methodsmentioning
confidence: 99%
“…For patch-clamp analysis, C57BL/6 mice were fed with Na ϩ -deficient diet (Ͻ0.01% Na ϩ , TD.90228, Envigo) for 1 wk to increase ENaC activity in the cortical collecting duct (CCD). The procedure for CCD isolation has been previously described (43). Briefly, kidneys were cut into thin slices (Ͻ1 mm) and placed into ice-cold solution containing (in mmol/L) 150 NaCl, 5 KCl, 1 CaCl2, 2 MgCl2, 5 glucose, and 10 HEPES (pH 7.35).…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that ClC-K2 activity in the intercalated cells is inversely related to dietary Cl − intake but not to aldosterone ( 45 ). Thus, it is plausible to propose that elevations of Ang II during volume depletion (which is also chloride depletion) increases ENaC-mediated sodium and pendrin/ClC-K2–dependent Cl − reabsorption by acting on principal and intercalated collecting duct cells, respectively ( 10 , 53 ). Furthermore, Ang II seems to be also critical to determine ClC-K2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II augments chloride reabsorption in the collecting duct by stimulating apical Cl − /HCO 3 − exchange ( 10 ) and basolateral Cl − exit via ClC-K2 ( Figs. 1 and 3 ) in intercalated cells and increases the apical ENaC-mediated sodium entry in principal cells ( 14 , 53 ). In this regard, the lack of stimulatory effects of Ang II on K ir 4.1/5.1 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation